A Study of Rehabillitated Mangrove Ecosystem in Different Planting Year to Estimate Tannin Extract Content in Northern Coast of Central Java - Erny Poedjirahajoe; Ragil Widyorini; Ni Putu Diana Mahayani (Jurnal Ilmu Kehutanan, 2011)
The research was conducted in the mangrove plantation areas of Pemalang and Rembang North coasts. From those two areas, mangrove vegetations with the same three plantation ages were chosen which were then divided into three zones from the sea. Tree density, height and diameter, the depth of sediment, water salinity and the content of organic matter were measured and assessed for each mangrove zones and plantation ages. In order to estimate the content of tannin extract of a mangrove tree, three mangrove trees of each plantation age were taken as samples. The wood of the trees were then peeled off, measured the weight and taken to the laboratory to analyze their tannin extract content. The content of tannin extract of the whole mangrove areas was obtained by multiplying the average of tannin extract content per tree with the vegetation density of those two mangrove areas. Varians analysis was employed to find out the significant different of the density three plantation ages of two mangrove rehabilitation areas. The results showed that for plantation years of 2002, the tannin extract content at both mangrove plantation areas of Pemalang and Rembang in averages was estimated to have a higher amount than those of plantation year 2003 and 2006. Respectively, the tannin extract content of plantation year of 2002 in Pemalang and Rembang were estimated to have 105.93 kg/ha and 159.23 kg/ha tannin extract. Mangrove vegetation with plantation year of 2006 in Pemalang contained 80.90 kg/ha, while for Rembang is 146.36 kg/ha.